STUDY OF MACRO AND MICRO ELEMENT COMPOSITION OF APPLE PLANT BY ICP-MS METHOD (Scientific journal of the Fergana State University, 2024)
Samples of leaves, roots, fruits, and soil of the growing «Semerenko» apple tree were analyzed by inductively coupled plasma mass spectrometry. The qualitative and quantitative content of 61 elements was determined in the studied plant samples. Of the identified elements, 5 are macroelements, 53 are microelements and 3 are toxic elements. The amount of macroelements calcium, potassium, phosphorus, magnesium, and sodium and microelements such as iron, strontium, aluminum, barium, copper, titanium, zinc, manganese, chromium, rubidium, and silver in the studied parts of the apple tree was determined. The amount of elements is greatest in the leaves of the plant and least in the fruits. The greatest amount of calcium is found in the roots and leaves, and potassium in the fruits. Potassium and calcium make up 93.4% of macroelements in fruits, the most in fruits are potassium (1056 µg/g), calcium (690 µg/g), and of the microelements iron (33 µg/g). Toxic elements found include arsenic, cadmium, and lead. In addition, the amount of elements in the soil where apple trees are grown was determined. Calcium, aluminum, iron, magnesium, potassium, sodium, phosphorus and titanium are found in large quantities in the soil.